Dissemination of Information Regarding Online Passport Queue Applications by Immigration Office Sukabumi - Bobby Briando; M. Fajar Ramadhan Rhouspamann (Jurnal Abdimas Imigrasi, 2020)
The Republic of Indonesia Travel Document is the identity of an Indonesian citizen (WNI) when traveling across the country, one of the travel documents is known to the public by the name of a passport. Passports are issued by authorized officials and are official documents that contain the identity of the owner to travel internationally. Apart from the passport function, the passport holder must also be able to take responsibility for the ownership of the passport itself. Nowadays the times continue to develop, public services are increasingly being improved so that the index of public satisfaction with the government especially those providing services continues to increase. Immigration as one of the government institutions that provide services makes breakthroughs related to the manufacture of passports, namely by the publication of an application called APAPO (Online Passport Registration Application). This application was created with the hope that it can be a solution to the problem that is often a public complaint, namely the queue of passport applicants who are staring at the Immigration Office, especially at the Immigration Office in Sukabumi. To introduce this breakthrough, community service related to online passport application registration has been carried out using socialization to each sub-district within the scope of the Sukabumi Immigration Office, which covers the areas of Sukabumi City, Sukabumi Regency, and Cianjur.